Energy, Natural Resources and Environmental Economics - Bjørndal, Endre; Bjørndal, Mette; Pardalos, Panos M.; Rönnqvist, Mikael (Energy Systems, 2010)
The book consists of a collection of articles (survey and research) describing the area of energy, natural resources and environmental economics. The contents of the book is divided into four sections. The first part considers petroleum and natural gas applications, taking up topics ranging from the management of incomes and reserves to market modeling and value chain optimization. The second and most extensive part studies applications from electricity markets, including analyses of marked prices, risk management, various optimization problems, electricity market design and regulation. The third part describes different applications in logistics and management of natural resources. Finally, the fourth part covers more general problems and methods arising within the area. The volume contains many examples from Nordic countries where there is knowledge and experience in managing natural resources.